Sensitivity Study of Surface Curvature in Characterisation Of Cartilage Mechanical Properties - Abd Latif, M.J.; Ismail, N.R.A.; Ramlan, R.; Mahmud, J.; Abdul Kadir, M.R. (Trans Tech Publications, 2013)

(untitled)
The mechanical properties of articular cartilage serve as important measures of tissue function or degeneration, and are known to change significantly with asteoarthritis. In previous computational studies, the cartilage surface of axisymmetric models was assumed to be flat in order to evaluate the cartilage behaviour. This assumption was inappropriate since the synovial joint possessed curvature geometrical shape and may contribute to the inaccurate in characterising the cartilage properties. Therefore, this study aims to examine the sensitivity of cartilage surface curvature of characterized cartilage biphasic properties using a combination of experimental and computational methods. Axisymmetric biphasic poroelastic finite element models were generated to measure cartilage surface radius and thickness. Based on the results, the smaller cartilage surface of 20 mm radius produced higher difference of the characterised properties where its generate 9% difference in the permeability and 5% difference in the elastic modulus, compared to the flat cartilage. Based on these results, it may indicate that the cartilage curvature will affect the characterised cartilage biphasic properties of elastic modulus and permeability.